Hubungan Tingkat Kecacatan dengan Derajat Depresi pada Penderita Kusta di SiCanang, Belawan, Sumatera Utara - Batubara, Dian Erisyawanty; Nuralita, Nanda Sari (Buletin Farmatera, 2022)
Leprosy and the disability it causes, have a negative stigma in community; however only a few reports have investigated the link between leprosy and psychiatric morbidity such as depression. This study aimed to asses correlation between leprosy disability grade and depression severity among people with leprosy in Sicanang, Belawan, North Sumatera. This study was unpaired categorical comparative analytic study and 54 participants were enrolled to this study. We found a high percentage of leprosys disability, 88,9% participants were having second grade leprosys disability that means the disability was obviously seen. We found that 29,63% participant suffered from a moderate depression, 14,82% with severe depression and 10,27% suffered from extreme depression. The correlation between disability grade and depression severity was analyzed with chi square test and p value was 0,182 which means that no significant relationship between disability grade and depression severity. Depression severity among people with leprosy in Sicanang was determined by patients self perception, spouse, onset of diagnosis and patients perception about their religion.